2012
DOI: 10.1161/circgenetics.112.963421
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Structural and Sarcomere Genes Associated With Cardiomyopathy Exhibit Marked Intolerance of Genetic Variation

Abstract: Background The clinical significance of variants in genes associated with inherited cardiomyopathies can be difficult to determine due to uncertainty regarding population genetic variation and a surprising amount of tolerance of the genome even to loss of function variants. We hypothesized that genes associated with cardiomyopathy might be particularly resistant to the accumulation of genetic variation. Methods and Results We analyzed the rates of single nucleotide genetic variation in all known genes from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…With insights gained from sequence data in many thousands of individuals in the general population, it has now become apparent that, in fact, a substantial proportion of human coding sequence variants are rare. A good example of this was provided in the data reported by Pan et al (2012), who looked at SNPs in coding regions of 46 cardiomyopathy genes in more than 5000 individuals in the ESP database and found that 9103 (91%) of the 9974 total variants were rare (minor allele frequency ,1%) and that 5448 (60%) of these were novel and seen only in one individual. In traditional Sanger-sequencing studies of selected candidate genes, any single high-impact variants identified have been assumed to be pathogenic.…”
Section: An Emerging Conundrum: Novel Functionally Deleterious Varianmentioning
confidence: 99%
“…With insights gained from sequence data in many thousands of individuals in the general population, it has now become apparent that, in fact, a substantial proportion of human coding sequence variants are rare. A good example of this was provided in the data reported by Pan et al (2012), who looked at SNPs in coding regions of 46 cardiomyopathy genes in more than 5000 individuals in the ESP database and found that 9103 (91%) of the 9974 total variants were rare (minor allele frequency ,1%) and that 5448 (60%) of these were novel and seen only in one individual. In traditional Sanger-sequencing studies of selected candidate genes, any single high-impact variants identified have been assumed to be pathogenic.…”
Section: An Emerging Conundrum: Novel Functionally Deleterious Varianmentioning
confidence: 99%
“…Even in a study as big as 5000 individuals, about half of the variants identified were unique to 1 individual. 2 In other words, a low allele frequency is a necessary, but in no way sufficient, criterion for a plausible disease-causing mutation in a dominant trait. Evolutionary conservation adds information, but it is a low bar because a high proportion of amino acid residues are conserved and because an impact of the mutation on the protein does not necessarily predict a causal role in a specific disease.…”
Section: Article See P 10mentioning
confidence: 99%
“…It is therefore crucially important to determine the extent of natural genetic variation and to distinguish 'background noise', particularly on a population and ethnicity basis, to define how much is disease-associated and therefore disease-modifying and/or disease-causative. For example, a study of general population exome data from the National Heart, Lung, and Blood Institute's Exome Sequencing Project has demonstrated that previously disease-associated mutations in the HCM genes were present in a higher frequency than expected for a purely monogenic disease model [32].…”
Section: The Need For Functional Characterisationmentioning
confidence: 99%